2021
DOI: 10.1002/biot.202100298
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antiviral activities with molecular docking study of chitosan/carrageenan@clove oil beads

Abstract: Background: Biopolymers are promising candidates that can be fabricated into hydrophilic matrices and used for many applications due to their distinctive properties such as non-toxic, biodegradable, biocompatibility, and low cost. A promising composite of chitosan and carrageenan with self-crosslinking has been prepared. Methods and Results:In this study, a rigorous approach for an inexpensive and nontoxic combination of different amounts of clove oil with two polyelectrolytes including chitosan and carrageena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Due to increasing antimicrobial resistance for common drugs, thus 15 mm. In the same accordance with our results, Dacrory et al [42] reported that CS/CRGs beads had antibacterial and antifungal activities against human pathogenic microbes. To increase the antimicrobial activity of CS/CRG, other materials are added to enhance the activity as metal nanoparticleas and essential oils.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
“…Due to increasing antimicrobial resistance for common drugs, thus 15 mm. In the same accordance with our results, Dacrory et al [42] reported that CS/CRGs beads had antibacterial and antifungal activities against human pathogenic microbes. To increase the antimicrobial activity of CS/CRG, other materials are added to enhance the activity as metal nanoparticleas and essential oils.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
“…Modification via carboxymethylation, oxidation and Micheal addition reaction can introduce new functional groups in the cellulose backbone including -OH, carboxyl (-COOH), cyano (-C=N), aldehyde (-CH=O) and tetrazole groups, leading to derivatives, such as carboxymethyl cellulose (CMC), methylcellulose (MC), dialdehyde cellulose (DAC) and hydroxyethyl cellulose (HEC), as summarised in Table 2 . Over the past years, because of the increasing demand for environmentally eco-friendly and biocompatible products, the possibility to chemically modify the cellulose has boosted great advances in material science and engineering, leading to the use of cellulose derivatives in promising fields of applications, such as pharmaceutical and biomedical [ 34 ], but also electronic [ 35 , 36 ], as well as a water treatment one [ 37 , 38 ].…”
Section: Cellulose and Cellulose Derivativesmentioning
confidence: 99%
“…l Antiviral activity: The antibacterial, antiviral, and molecular docking activities of clove oil with two polyelectrolytes, chitosan and carrageenan, in the form of beads, was examined. The maximum nontoxic concentration (MNTC) of chitosan/ carrageenanclove oil beads was found to be 31.25 g ml, which demonstrated promising antiviral activity against Herpes simplex virus-1 (HSV-1) and was significantly higher than chitosan/carrageenan without clove oil, which had an antiviral activity of 82.94 percent and 57.64 percent [20]. In another research, eugenin was discovered to be a strong inhibitor of the Dengue virus protease (DENV).…”
Section: Contraindicationsmentioning
confidence: 99%